Representasi Defining Modern Womanhood: Cosmopolitan's Strategic Cover Choices and Their Impact on Young Women's Identity - Ratnaningtyas, Rr. Pramesthi (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Women's beauty and physical perfection are the main points for presenting their figures in mass media. Women are considered the most effective means of connecting audience interaction in persuading. Cosmopolitan is a media that often presents female public figures on its magazine cover. Cosmopolitan is here to create and transform brands into authentic conversation destinations about important things to the audience. Cosmopolitan predominantly uses foreign model covers. However, in July and August 2022, Cosmopolitan presented covers with photos of female singers, namely Agnez Mo and Isyana. Both are female singers whose abilities are recognized in Indonesia. The digital cover was studied using a descriptive qualitative approach with Charles Sanders Peirce's semiotics as an analytical tool. The results show that the representation of modern women presented by Cosmopolitan is a simple appearance without removing other important elements in fashion. Among them are comfort and an elegant and classy impression. The clothes used represent the identity of public figures in the eyes of the public. In addition, it brings innovation and becomes a dialogue regarding changes in how modern women think and behave. Modern women must understand the importance of being wise on social media, being themselves, and being inspired through their work. These three things are realized as a result of a healthy mentality.